PENGARUH LATIHAN SHOOTING TERHADAP TINGKAT AKURASI SHOOTING PEMAIN SSB SALUT FC DI KABUPATEN PESISIR SELATAN - Ahmad, Rapi; Atradinal, Atradinal; Asnaldi, Arie; Pra Adha, Ozha Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low shooting accuracy can reduce players’ effectiveness in converting goal-scoring opportunities and remains an important technical issue in youth football development. This study aimed to examine the effect of shooting training on the shooting accuracy of SSB SALUT FC players in Pesisir Selatan Regency. The study employed a quantitative pre-experimental approach using a one-group pretestposttest design. The sample consisted of 29 SSB SALUT FC players who completed a pretest, participated in a systematically structured shooting training program, and subsequently completed a posttest. Shooting accuracy was measured using a target-zone-based instrument designed to objectively assess shot direction and accuracy. Data were analyzed using the Shapiro–Wilk normality test, pairedsamples t-test, and effect size analysis. The results showed that the mean shooting accuracy score increased from 10.93 (SD = 4.423) at pretest to 18.38 (SD = 2.470) at posttest, representing an improvement of 7.45 points. The paired-samples t-test revealed a statistically significant difference between pretest and posttest scores, t(28) = −8.267, p < .001. Cohen’s d of 1.535 indicated a large effect size. Thus, systematic and structured shooting training was associated with a statistically significant and practically meaningful improvement in players’ shooting accuracy. Shooting training should therefore be systematically integrated into youth football development programs by emphasizing technical accuracy, repetition, target variation, progressive difficulty, and regular evaluation.